Approaching White-Light Emission from a Phosphorescent Trinuclear Gold(I) Cluster by Modulating Its Aggregation Behavior - Ni, Wen-Xiu; Li, Mian; Zheng, Ji; Zhan, Shun-Ze; Qiu, Yu-Min; Ng, Seik Weng; Li, Dan (Angewandte Chemie International Edition, 2013)
White light: [{Au(L)}3] (L=3‐(2‐thienyl)pyrazolate) gives dual emission, one from an organic chromophore the other from aurophilic stacking interactions. The resulting blue–green and orange–red emissions can be tuned to approach white‐light by modulating the aggregation behavior of the cluster.